2019
DOI: 10.1103/physreva.99.042702
|View full text |Cite
|
Sign up to set email alerts
|

Cold reactive and nonreactive collisions of Li and Rb with C2 : Implications for hybrid-trap experiments

Abstract: We present a theoretical investigation of cold reactive and non-reactive collisions of Li and Rb atoms with C − 2 . The potential energy surfaces for the singlet and triplet states of the Li-C − 2 and Rb-C − 2 systems have been obtained using the CASSCF/ic-MRCI+Q approach with extended basis sets. The potential energy surfaces are then used to investigate the associative detachment reaction and to calculate rotationally inelastic cross sections at low collision energies by means of the close-coupling method. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The results obtained here can also be usefully compared to those yielded by similar systems. For example, the cross-sections and rate coefficients for rotationally inelastic transitions in the case of C − 2 colliding with Li and Rb were found to be quite similar to each other [26] and far larger (between 4 and 10 times) than those reported here for the p-H 2 (j=0) partner, as a consequence of the much stronger interactions shown by the former partners as we had mentioned earlier in this paper. The CN − anion can also be considered for comparison since we had found that its rotationally inelastic collisions with p-H 2 (j = 0) and with Ar yield cross-sections and rate coefficients which are more similar with each other than what we have found with C − 2 , particularly for the low N transitions [34].…”
Section: Rotationally Inelastic Scattering Cross-sections and Rate Constantssupporting
confidence: 81%
See 2 more Smart Citations
“…The results obtained here can also be usefully compared to those yielded by similar systems. For example, the cross-sections and rate coefficients for rotationally inelastic transitions in the case of C − 2 colliding with Li and Rb were found to be quite similar to each other [26] and far larger (between 4 and 10 times) than those reported here for the p-H 2 (j=0) partner, as a consequence of the much stronger interactions shown by the former partners as we had mentioned earlier in this paper. The CN − anion can also be considered for comparison since we had found that its rotationally inelastic collisions with p-H 2 (j = 0) and with Ar yield cross-sections and rate coefficients which are more similar with each other than what we have found with C − 2 , particularly for the low N transitions [34].…”
Section: Rotationally Inelastic Scattering Cross-sections and Rate Constantssupporting
confidence: 81%
“…It is also significant to note that while the PESs and corresponding Legendre expansion coefficients for the C − 2 /H 2 and C − 2 /Ar systems discussed here show a relatively strong interaction, far larger than C − 2 /He for example, the interactions of the same anion with the open-shell, highly polarisable atoms like Li and Rb have a much stronger interactions. For these systems, the global minima of their corresponding PESs occur at perpendicular (T-shaped) atom-molecule geometries and are around −18, 000 for C − 2 /Li and −10, 500 cm −1 for C − 2 /Rb with corresponding V 0 term minima of around 12,000 (1.5 eV) and 8000 cm −1 (1.0 eV) respectively [26].…”
Section: − 2 /H 2 Ab Initio Calculations and Potential Energy Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…This last achievement could allow the efficient production of antihydrogen atoms, currently being investigated for tests of fundamental physics such as CPT invariance [11] and the weak equivalence principle [12]. The diatomic carbon molecular anion C 2 − has been a model system for decades, attracting a great deal of experimental [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and theoretical [8,[28][29][30][31][32][33][34][35][36] work. Its bound electronically excited states [32] are unusual for an anion, which is a consequence of the high electron affinity of neutral C 2 of around 3.3 eV [17,21] in combination with the open shell character of the electronic configuration of carbon dimers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it possesses several electronic excited states that could be used in laser-cooling schemes [8] as well as to explore excited-state dynamics. In a recent work, we have studied the interaction of C − 2 with Li and Rb atoms and concluded that the associative detachment reaction should proceed with a rate much smaller than the Langevin rate provided that the ultracold atoms are in their ground state [9]. In section 2 we discuss the potential energy surfaces (PESs) that were constructed for these systems.…”
Section: Introductionmentioning
confidence: 99%